2021
DOI: 10.1111/lam.13456
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall thickness and the molecular mechanism of heterogeneous vancomycin‐intermediateStaphylococcus aureus

Abstract: Significance and impact of the study: We isolated a heterogeneous vancomycin (VAN)-intermediate Staphylococcus aureus (hVISA) strain, and we demonstrated that the cell wall of the hVISA strain was significantly thicker than that of ordinary MRSA strains. The upregulated expression of glmS, vraR/S, sgtB, murZ and PBP4 genes related to cell wall synthesis might be the molecular mechanism underlying the cell wall thickening of the hVISA strain and might be related to its reduced sensitivity to VAN. These results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…This may be due to their similarity in tolerance to low level vancomycin (both the hVISA and the VISA had higher PAP-AUC values than those of the VSSA) [12]. In addition, our previous study and a recent report showed that the hVISA isolates also had thickening cell wall, though not as thick as that of the VISA isolates [20,21]. The vancomycin MIC of the VISA isolates in this study was slightly higher than those of the hVISA and the VSSA isolates.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This may be due to their similarity in tolerance to low level vancomycin (both the hVISA and the VISA had higher PAP-AUC values than those of the VSSA) [12]. In addition, our previous study and a recent report showed that the hVISA isolates also had thickening cell wall, though not as thick as that of the VISA isolates [20,21]. The vancomycin MIC of the VISA isolates in this study was slightly higher than those of the hVISA and the VSSA isolates.…”
Section: Discussionmentioning
confidence: 77%
“…Though the target site of vancomycin is D-alanyl-D-alanine residue of the cell wall [23], it may have indirect effect to other intracellular components of the bacterial cells such as cell membrane, ribosome, and DNA [23]. The VISA and the hVISA cells had thickening cell wall and increasing free D-alanyl-Dalanine residues, leading to vancomycin blockage from reaching its target site [21,24]. This may be the reason of lower stress response of the VISA and the hVISA to vancomycin than that of the VSSA.…”
Section: Discussionmentioning
confidence: 99%
“…Then, shotgun proteomics LC-MS/MS analysis identified all of the pulled-down proteins, and we found 18 differential proteins ( Figure 1 ). GO functional analysis revealed that GlmS, a metabolite interconversion enzyme, has catalytic activity and participates in cellular processes and metabolic processes [ 10 , 32–34 ]. KEGG pathway analysis indicated that GlmS may be related to the N-acetylglucosamine metabolism pathway, which can affect the cell wall synthesis of S. aureus [ 10 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…This discovery is very unexpected and interesting. To date, research on glmS has mainly focused on cell wall synthesis, drug resistance, and the development of antibiotic targets [ 11 , 32 , 34 ], but no research has shown its roles in the global regulation and pathogenicity of S. aureus thus far. In previous studies, riboswitches have been classified as a family of 5’-untranslated mRNA regions mostly found in bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Cell wall thickness is influenced by autolysis, peptidoglycan crosslinking and cell wall synthesis (42,43). In S. aureus, cell wall synthesis can increase upon cell wall stress induced by antibiotics.…”
Section: Discussionmentioning
confidence: 99%